2007
DOI: 10.1002/j.2158-1592.2007.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Using E‐business Technology: The Supplier Perspective

Abstract: The use of e‐business technologies between supply chain organizations has primarily been examined from the viewpoint of buying firms or retailers, with little attention given to the benefits accrued to suppliers. Further, previous studies have been limited to either financial or marketing performance measures, or a narrow range of operational measures. This study builds on research in this area by testing a model of the relationship between supplier use of e‐business technologies in communication with their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 38 publications
0
40
1
3
Order By: Relevance
“…Bagchi et al (2005) reported the major benefits of collaboration as the reduction in logistic cost and better order fulfillment rate. Sanders (2007) discussed the positive effect of collaboration on quality, cost, and delivery. Zhang (2010, 2011) identified the benefits in the way like the growth of sale and profit margin.…”
Section: Benefits Of Supply Chain Collaborationmentioning
confidence: 99%
“…Bagchi et al (2005) reported the major benefits of collaboration as the reduction in logistic cost and better order fulfillment rate. Sanders (2007) discussed the positive effect of collaboration on quality, cost, and delivery. Zhang (2010, 2011) identified the benefits in the way like the growth of sale and profit margin.…”
Section: Benefits Of Supply Chain Collaborationmentioning
confidence: 99%
“…The approach is treated both explicitly and implicitly in logistics articles and textbooks. Sanders (2007) claims that SCM has a systems view because all activities and functions that are needed to bring a product or service to market are considered. Arlbjørn and Halldorsson (2002) use the term hard core to explain what is unchangeable and to illustrate what the knowledge within logistics is all about.…”
Section: The Systems Approach In Logisticsmentioning
confidence: 99%
“…Les activités analysées sont la gestion de stock (Kull et al, 2013 ;Taylor et al, 2004 ;Rabinovich 2003Rabinovich , 2004Rabinovich , 2011, les retours (Mollenkopf et al, 2007 ;Rao et al, 2014, Kokkinaki et al, 1999, le management des systèmes d'information (Waller and Fawcett, 2013 ;Wang, 2008Sanders, 2007).…”
Section: Activités Et Acteursunclassified